2021
DOI: 10.1016/j.optom.2020.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Blue-yellow deficiencies in young moderate smokers

Abstract: Purpose To evaluate whether tobacco affects color vision in young moderate smokers. Methods Chromatic mechanisms of 13 moderate smokers (10–20 cigarettes/day and at least 5 years smoking) and 17 non-smokers in the 18–35 age range were assessed with the Farnsworth-Munsell 100-hue (FM100h) test and short wavelength automated perimetry (SWAP). Results FM100h Total Error Scores (TES) were higher for smokers, and although differences were not sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…Previous literature reports damage in the achromatic, red-green, or blue-yellow [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] mechanisms, but comparisons between mechanisms are scarce. The published data show variability: although global damage is reported, results are not always consistent with a selective loss pattern, and when this selective loss is found, there is no agreement on which is the more affected mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous literature reports damage in the achromatic, red-green, or blue-yellow [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 ] mechanisms, but comparisons between mechanisms are scarce. The published data show variability: although global damage is reported, results are not always consistent with a selective loss pattern, and when this selective loss is found, there is no agreement on which is the more affected mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on red-on-white [ 13 ] or blue-yellow [ 14 , 18 ] (SWAP) perimetry with smokers classified according to the number of cigarettes smoked per day, found foveal sensitivity losses in moderate smokers (maximum 20 cig/day) [ 14 ], and paracentral scotomas in chronic smokers (minimum 20 cig/day) [ 13 ]. Losses in the blue-yellow mechanism, however, are not significant in young moderate smokers, showing a possible effect of age [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown an association between smoking, impaired color vision, and decreased contrast sensitivity. [15][16][17][18] Recent research by Han et al showed a relationship between urine cotinine levels and visual impairment, which was seen in a decrease in visual acuity. 19 So, it is important to see the association between cotinine levels with color vision before a decrease in vision occurs.…”
Section: Discussionmentioning
confidence: 99%